Association Between Allergen Sensitization and Anaphylaxis in Patients Visiting a Pediatric Emergency Department - Won Seok Lee; Lily Myung-Jin Cha; Man Yong Han; Kyung Suk Lee (Frontiers Media S.A., 2021)
Background and Objectives: Anaphylaxis, a severe allergic disease, can be triggered by various causes. This study investigated the association between allergic sensitization and anaphylactic symptoms and the severity of anaphylaxis in children.Patients and Methods: A retrospective review of 107 pediatric patients with anaphylaxis was performed between January 1, 2015, and December 31, 2017; 74 patients underwent allergen testing for specific immunoglobulin E. Allergic sensitizations and associations with anaphylactic symptoms and severity were investigated.Results: Overall, 64 (86.5%) patients were sensitized to food or inhalant allergens. In children under 2 years of age, 90.5% were sensitized to food (P = 0.001); in those over 6 years of age, 84.6% were sensitized to inhalant allergens (P = 0.001). Milk sensitization was significantly associated with severe anaphylaxis (P = 0.036). The following symptoms showed significant associations with certain allergen sensitizations: facial edema with food; wheezing with milk; dyspnea with mite, etc. Certain allergen sensitizations presenting as risk factors for anaphylactic symptoms: wheat (adjusted odds ratio [aOR] = 4.644, P = 0.044) and nuts (aOR=3.614, P = 0.041) for wheezing, nuts (aOR=5.201, P = 0.026) for dyspnea, and milk (aOR=4.712, P = 0.048) for vomiting.Conclusion: The allergen sensitization status differed according to the age of the children experiencing anaphylaxis. The severity, symptoms, and signs of anaphylaxis differed depending on the allergen sensitization status.